Representation and scalability of hierarchical abstractions in robustness diagram with loop and time controls Edu S. Pestilos; Jasmine A. Malinao, adviser. - Petilos, Edu S.; Malinao, Jasmine A. (2024)
The Robustness Diagram has a notational backbone that was utilized to develop a powerful modeling technique-- The Robustness Diagram with Loop and Time Controls. It supports modeling of complex systems while representing all three workflow dimensions. However, due to its limited number of robustness stereotypes, using this modelling technique gets trickier as the system being represented gets more complex, failing to capture every system behavior accurately and explicitly. Having a wider set of robustness stereotypes and their relationship types in Robustness Diagram with Loop and Time Controls help in representing complex systems. It provides better flexibility in creating such models which are easier to understand and support representation of more details in the overall behavior of complex systems.
This study proposes an enrichment to Robustness Diagram with Loop and Time Controls components such that the representation of hierarchical abstractions e.g. aggregations, compositions, generalizations, and specializations are established. Explicit representations of XOR-splits, multi-module interactions, and multilevel systems are also proposed. Moreover, a modification to the activity extraction algorithm in accordance with the enrichment is proposed. Some existing real-world systems or workflows modelled using flowcharts, Robustness Diagram with Loop and Time Controls, and its predecessor, the Robustness Diagram, are used in modelling with the proposed enrichment, then later compared and contrasted to highlight the improvement in the readability of the latter models. Furthermore, the enrichment was validated in an artificial manner through dummy test cases to demonstrate how accurate the system behaviors are captured.
Undergraduate thesis (B.S. Computer Science) -- University of the Philippines, Tacloban.